2008
DOI: 10.1007/s10440-008-9229-z
|View full text |Cite
|
Sign up to set email alerts
|

What is Q-Curvature?

Abstract: Branson's Q-curvature is now recognized as a fundamental quantity in conformal geometry. We outline its construction and present its basic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…In this appendix, we give a Kazdan-Warner type condition for the solvability of (1.4). In the Euclidean case, such condition was obtained in [1], [25], [26] and [6]. Let us identify H n with the set C n × R = R 2n+1 = {(x 1 , y 1 , .…”
Section: By Oddness It Holds Thatmentioning
confidence: 99%
“…In this appendix, we give a Kazdan-Warner type condition for the solvability of (1.4). In the Euclidean case, such condition was obtained in [1], [25], [26] and [6]. Let us identify H n with the set C n × R = R 2n+1 = {(x 1 , y 1 , .…”
Section: By Oddness It Holds Thatmentioning
confidence: 99%
“…Significant mathematical progress was made when Fefferman and Graham [FG02] showed that for Poincaré-Einstein structures (Euclidean signature, asymptotically AdS, Einstein manifolds), the renormalized volume anomaly recovered Branson's Q-curvature [B95] for the boundary manifold. This is an important invariant of conformal geometries (see [GJ07,DM08] and the reviews [BG08,CEOY08]). The renormalized volume is usually obtained by computing a Fefferman-Graham coordinate expansion of a bulk metric tensor solving, to some order, a bulk problem with boundary data at a conformal infinity Σ.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the explicit form of the mentioned decomposition of the critical heat kernel coefficients is not known, and the general principles which may connect heat kernel coefficients of P 2 (and other conformally covariant operators) and Q-curvatures have not yet been found. For a brief introduction to the numerous aspects of Q-curvature see [CEOY08].…”
Section: Introduction and Formulation Of The Main Resultsmentioning
confidence: 99%